2013
DOI: 10.4103/0976-7800.109633
|View full text |Cite
|
Sign up to set email alerts
|

Are women satisfied when using levonorgestrel-releasing intrauterine system for treatment of abnormal uterine bleeding?

Abstract: Aim:To determine the efficacy of levonorgestrel intrauterine system (LNG IUS) in treatment of abnormal uterine bleeding (AUB) in women over 35 years and to determine satisfaction of users of LNG IUS in case of AUB.Materials and Methods:This was a multicentric, retrospective, and observational study. Case records of patients with AUB from the hospitals in Pune, Delhi, and Gurgaon for the last 6 years were examined. Records of 80 women who had an LNG IUS inserted were included. The chief complaints and their dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…10 The overall satisfaction scores were significantly more in the LNG-IUS group as compared to the hysterectomy group with 90% women being satisfied with the treatment in the LNG-IUS group and only 50% being satisfied in the hysterectomy group. 10 A total of 70.3% patients with fibroids were satisfied and 82.4% said that they would recommend this treatment to other users as reported by Mansukhani N et al 6…”
Section: Discussionmentioning
confidence: 91%
“…10 The overall satisfaction scores were significantly more in the LNG-IUS group as compared to the hysterectomy group with 90% women being satisfied with the treatment in the LNG-IUS group and only 50% being satisfied in the hysterectomy group. 10 A total of 70.3% patients with fibroids were satisfied and 82.4% said that they would recommend this treatment to other users as reported by Mansukhani N et al 6…”
Section: Discussionmentioning
confidence: 91%
“…Overall, Indian studies with LNG-IUS, have consistently shown high satisfaction rates ranging from 80-96%. 5,20,21,24 Though there is no data on the efficacy and safety of LNG-IUS versus, other medical therapy, the results from Asia-Pacific study has shown superiority of LNG-IUS over conventional medical treatment. The most common reasons for discontinuation of LNG-IUS were adverse event or either bleeding.…”
Section: Safety Of Lng-ius Is Well Established In Indian Womenmentioning
confidence: 99%
“…The details of these studies are given in Table 1. 5,[19][20][21][22][23][24] Gupta et al reported 97% reduction in menstrual blood loss with LNG-IUS, at the end of one year. 20 Anemia is very common in women suffering from heavy monthly bleeding.…”
Section: Indian Evidence Of Lng-iusmentioning
confidence: 99%
See 1 more Smart Citation
“…In study by Nina manasukani et al [17] cases with adenomyosis seemed to respond very well and most of the patients were asymptomatic (52.63%) and 26.3% had amenorrhea at 6 months and 31.57% at 12 months. In many studies, though it was found that LNG IUCD is very effective in treatment of abnormal uterine bleeding, very few patients opting for IUCD in our setup as most of the patients are belonging to low socioeconomic status.…”
Section: Outcome In Uterine Fibroidsmentioning
confidence: 99%